Negative electrode material and preparation method and application thereof

By using the silicon-based material core and carbon layer coated negative electrode material in lithium-ion batteries, the problems of lithium-ion battery capacity, energy density and cycle life are solved, and higher battery performance and longer service life are achieved.

CN118658981BActive Publication Date: 2025-02-25BTR NEW MATERIAL GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411136297.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-02-25
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The capacity and energy density of existing lithium-ion batteries are poor, the first charging and discharging efficiency is low and the cycle life is short.

Method used

The negative electrode material including a silicon-based material core and a cladding layer is used. The cladding layer includes a carbon layer, which is prepared by microwave reaction and laser bombardment, and the charging and discharge expansion coefficients are controlled within a specific range.

Benefits of technology

It improves the first Coulomb efficiency, battery capacity, energy density and cycling performance of lithium-ion batteries, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118658981B_ABST
    Figure CN118658981B_ABST
Patent Text Reader

Abstract

The present application provides a negative electrode material and a preparation method and application thereof, wherein the negative electrode material comprises a silicon-based material core and a coating layer at least partially coated on the surface of the silicon-based material core, and the first charging expansion coefficient, the first discharging expansion coefficient, the second charging expansion coefficient, and the second discharging expansion coefficient of the negative electrode material meet the following conditions: 0.016≤≤0.025; 0.020≤≤0.030; 0.0008≤≤0.002; 0.003≤≤0.0036. Based on the negative electrode material of the present application, the problem of poor capacity and energy density and low initial efficiency of lithium-ion batteries in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery electrode materials, and in particular to a negative electrode material and a preparation method and application thereof. Background Art

[0002] The negative electrode material is one of the most critical materials that affect the capacity and energy density of lithium-ion batteries. Existing lithium-ion batteries mainly use graphite negative electrode materials, whose theoretical specific capacity is 372mAh / g, and the specific capacity of high-end graphite materials on the market can reach 360-365mAh / g, so there is no greater room for development. With the increasing demand for energy storage effects, silicon-based materials are considered to be promising lithium-ion battery negative electrode materials due to their high theoretical specific capacity, and have been widely studied in recent years. Therefore, using silicon-based materials to replace pure graphite negative electrodes has become one of the effective ways to increase the specific capacity of negative electrodes, but the poor electronic conductivity of silicon and the huge volume expansion problem during the charging and discharging process lead to poor battery capacity and energy density, and low cycle life, which hinders its commercial application. Compared with silicon, the volume expansion of silicon oxide materials during lithium insertion is greatly reduced, but it also has a high theoretical specific capacity (>2000mAh / g) and low preparation cost, so it has become a very promising negative electrode material. However, silicon oxide materials will generate inactive products such as Li2O and Li4SiO4 during lithium insertion, which will cause some Li to lose activity, resulting in low initial charge and discharge efficiency (<70%), which seriously affects its practical application. Therefore, it is of great significance to develop battery materials with high battery capacity and energy density, high initial charge and discharge efficiency and long cycle life. Summary of the invention

[0003] The main purpose of the present application is to provide a negative electrode material and a preparation method and application thereof, so as to solve the problems of poor capacity, energy density, low initial charge and discharge efficiency and low cycle life of lithium-ion batteries in the prior art.

[0004] In order to achieve the above object, according to one aspect of the present application, a negative electrode material is provided, the negative electrode material comprising a silicon-based material core and a coating layer at least partially coated on the surface of the silicon-based material core, and a first charging expansion coefficient K of the negative electrode material c1 , the first discharge expansion coefficient K f1 , the second charging expansion coefficient K c2 , the second discharge expansion coefficient K f2 The following conditions are met:

[0005] 0.016≤K c1 ≤0.025;

[0006] 0.020≤K f1 ≤0.030;

[0007] 0.0008≤K c2 ≤0.002;

[0008] 0.003≤K f2 ≤0.0036;

[0009]

[0010] 3≤N1≤5;

[0011] 4≤N2≤20;

[0012] Among them, V c0 V is the expansion rate of the negative electrode material after the first cycle of charging during the cyclic charge and discharge process; f0 V is the expansion rate of the negative electrode material after the first discharge cycle in the cyclic charge and discharge process; c1 V is the expansion rate of the negative electrode material after the N1th cycle of charging and discharging is completed; V f1 V is the expansion rate of the negative electrode material after the N1th cycle of discharge during the cyclic charge and discharge process; c2 V is the expansion rate of the negative electrode material after the N2th cycle of charging is completed during the cyclic charge and discharge process; f2 It is the expansion rate of the negative electrode material after the N2th discharge in the cyclic charge and discharge process.

[0013] Furthermore, N1=3, N2=20.

[0014] Furthermore, V0, V c1 、V f1 、V c2 、V f2 They were obtained by in-situ detection.

[0015] Further, the coating layer includes a carbon layer.

[0016] Furthermore, the silicon-based material includes at least one of silicon, silicon oxide and silicate, and the general formula of silicon oxide is SiO x , 0<x≤2.

[0017] Furthermore, based on 100% of the mass of the negative electrode material, the mass of the carbon layer is 2% to 6%.

[0018] Furthermore, the compaction density of the negative electrode material is 1.2 g / cm 3 Up to 1.5g / cm 3 , bulk density is 0.4g / cm 3 Up to 0.65g / cm 3 , true density is 2.0g / cm 3 Up to 2.5g / cm 3.

[0019] Furthermore, the compaction density of the negative electrode material meets 5.4×10 9 <1 / [1.33π×(extreme value / 2) 3 × compacted density] <1.01×10 10 The bulk density of the negative electrode material meets 9.5×10 9 <1 / [1.33π×(extreme value / 2) 3 × bulk density] <2.8×10 10 , the true density of the negative electrode material meets 2.2×10 9 <1 / [1.33π×(extreme value / 2) 3 × true density] <6.0×10 9 .

[0020] Furthermore, the powder conductivity of the negative electrode material was tested using a powder conductivity instrument. When the pressure was 20 kN, the tested powder conductivity was greater than 1 S / cm.

[0021] Furthermore, the contact angle of the negative electrode material is 140° to 180°.

[0022] According to another aspect of the present invention, there is provided a method for preparing a negative electrode material, comprising the following steps:

[0023] A first mixed material comprising elemental silicon powder and silicon dioxide powder is prepared, the first mixed material is placed in a microwave reaction furnace, and under vacuum conditions, the temperature in the microwave reaction furnace is raised to 1300° C. to 2000° C. at a heating rate of 15° C. / min to 25° C. / min, a mixed gas is obtained by reaction, and the mixed gas is condensed and then ground to obtain silicon-based material powder; wherein the molar ratio of elemental silicon in the elemental silicon powder to silicon dioxide in the silicon dioxide powder is (1.5-2.5):1;

[0024] The silicon-based material powder is mixed with a carbon source to obtain a second mixed material, and the second mixed material is subjected to laser bombardment treatment to obtain a negative electrode material;

[0025] The negative electrode material includes a silicon-based material core and a coating layer at least partially coated on the surface of the silicon-based material core. The first charging expansion coefficient K of the negative electrode material is c1 , the first discharge expansion coefficient K f1 , the second charging expansion coefficient K c2 , the second discharge expansion coefficient K f2 The following conditions are met:

[0026] 0.016≤K c1 ≤0.025;

[0027] 0.020≤K f1 ≤0.030;

[0028] 0.0008≤K c2 ≤0.002;

[0029] 0.003≤K f2 ≤0.0036;

[0030]

[0031] 4≤N2≤20;

[0032] Among them, V c0 V is the expansion rate of the negative electrode material after the first cycle of charging during the cyclic charge and discharge process; f0 V is the expansion rate of the negative electrode material after the first discharge cycle in the cyclic charge and discharge process; c1 V is the expansion rate of the negative electrode material after the N1th cycle of charging and discharging is completed; V f1 V is the expansion rate of the negative electrode material after the N1th cycle of discharge during the cyclic charge and discharge process; c2 V is the expansion rate of the negative electrode material after the N2th cycle of charging is completed during the cyclic charge and discharge process; f2 It is the expansion rate of the negative electrode material after the N2th discharge in the cyclic charge and discharge process.

[0033] Further, the coating layer includes a carbon layer.

[0034] Furthermore, the silicon-based material includes at least one of silicon, silicon oxide and silicate, and the general formula of silicon oxide is SiO x , 0<x≤2.

[0035] Furthermore, the particle size D50 of the silicon-based material powder is 5 μm to 10 μm.

[0036] Furthermore, the carbon source is selected from one or more of asphalt, natural graphite, and artificial graphite.

[0037] Furthermore, taking the sum of the mass of the silicon-based material powder and the carbon element in the carbon source as 100%, the mass of the carbon element in the carbon source is 2% to 6%.

[0038] Furthermore, the laser wavelength in the laser bombardment treatment is 1000nm to 1200nm.

[0039] Furthermore, a nanosecond pulse fiber laser is used for laser bombardment treatment, the pulse duration is 60ns to 100ns, and the laser bombardment treatment time is 1h to 5h.

[0040] Furthermore, the particle size D50 of the silicon dioxide powder is 1 μm to 2 μm.

[0041] Furthermore, the particle size D50 of the elemental silicon powder is 1 μm to 2 μm.

[0042] Furthermore, the microwave reaction furnace is evacuated to below 1 Pa, and then heated.

[0043] Further, condensation is performed under negative pressure conditions.

[0044] Furthermore, the microwave reaction time in the microwave reaction furnace is 2h to 14h.

[0045] According to another aspect of the present invention, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode active material layer bonded to the negative electrode current collector, wherein the active layer comprises the above negative electrode material or the negative electrode material prepared according to the above method for preparing the negative electrode material.

[0046] Furthermore, the negative electrode active material layer further includes graphite.

[0047] Furthermore, the graphite is selected from at least one of natural graphite, artificial graphite and modified graphite.

[0048] Furthermore, the modified graphite is selected from expanded graphite, oxidized graphite or a mixture of the two.

[0049] According to another aspect of the present invention, a lithium-ion battery is provided. The lithium-ion battery comprises the negative electrode sheet as described above.

[0050] By applying the technical solution of the present application, in the early stage of cyclic charge and discharge tests, the negative electrode material with an expansion coefficient within a certain numerical range can improve the ability of lithium ion batteries to smoothly remove and insert lithium during the initial and subsequent charge and discharge processes, thereby making the lithium ion battery prepared from the negative electrode material have a higher initial coulombic efficiency, battery capacity, energy density and cycle performance; in addition, in the early stage of cyclic charge and discharge tests, the negative electrode material with an expansion coefficient within a certain numerical range can effectively avoid the destruction of the material structure and mechanical crushing caused by significant volume expansion, thereby extending the battery life.

[0051] The negative electrode material of the present application can improve the initial coulombic efficiency, battery capacity, energy density and cycle performance of lithium-ion batteries, and extend the battery life. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0053] Figure 1 A schematic structural diagram of an electrode assembly is shown;

[0054] Figure 2shows a SEM image of the negative electrode material prepared in Example 1;

[0055] Figure 3 shows the XRD pattern of the negative electrode material prepared in Example 1;

[0056] Figure 4 The negative electrode material prepared in Example 1 is shown as a line graph of the expansion rate of the negative electrode material after each cycle of charging during the cyclic charge and discharge process, and a line graph of the expansion rate of the negative electrode material after each cycle of discharging. DETAILED DESCRIPTION

[0057] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0058] An embodiment of the present application provides a secondary battery, such as a lithium-ion battery, a sodium-ion battery, etc., comprising a housing, an electrode assembly, and an electrolyte, wherein the electrode assembly and the electrolyte are both located in the housing.

[0059] The shell can be a packaging bag encapsulated by a packaging film (such as an aluminum-plastic film), such as a soft-pack battery. In some embodiments, the secondary battery can also be a steel shell battery, an aluminum shell battery, etc.

[0060] like Figure 1 As shown, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is disposed between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In some embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0061] The positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active layer 12 provided on at least one surface of the positive electrode current collector 11. The positive electrode current collector 11 can be made of aluminum foil or nickel foil, etc., or it can be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and the polymer substrate. The positive electrode active layer 12 contains a positive electrode active material, and the positive electrode active material includes a compound that can reversibly embed and deintercalate metal ions. In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5O4) or at least one of lithium iron phosphate (LiFePO4).

[0062] The negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector. The negative electrode current collector 21 can use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or can be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer includes a negative electrode material.

[0063] As described in the background technology, the existing negative electrode materials have the problems of poor battery capacity and energy density and low cycle life. In order to solve the above problems, according to one aspect of the present application, a negative electrode material is provided, the negative electrode material includes a silicon-based material core and a coating layer at least partially coated on the surface of the silicon-based material core, and the first charging expansion coefficient K of the negative electrode material is c1 , the first discharge expansion coefficient K f1 , the second charging expansion coefficient K c2 , the second discharge expansion coefficient K f2 The following conditions are met:

[0064] 0.016≤K c1 ≤0.025;

[0065] 0.020≤K f1 ≤0.030;

[0066] 0.0008≤K c2 ≤0.002;

[0067] 0.003≤K f2 ≤0.0036;

[0068]

[0069] 3≤N1≤5;

[0070] 4≤N2≤20;

[0071] Among them, V c0 V is the expansion rate of the negative electrode material after the first cycle of charging during the cyclic charge and discharge process; f0 V is the expansion rate of the negative electrode material after the first discharge cycle in the cyclic charge and discharge process; c1 V is the expansion rate of the negative electrode material after the N1th cycle of charging and discharging is completed; V f1 V is the expansion rate of the negative electrode material after the N1th cycle of discharge during the cyclic charge and discharge process; c2 V is the expansion rate of the negative electrode material after the N2th cycle of charging is completed during the cyclic charge and discharge process; f2It is the expansion rate of the negative electrode material after the N2th discharge in the cyclic charge and discharge process.

[0072] In order to obtain a lithium-ion battery with high battery capacity, high energy density and good cycle performance, the present application provides a negative electrode material. In the early cycle charge and discharge test, the negative electrode material with an expansion coefficient in a certain numerical range can improve the lithium-ion battery's ability to smoothly remove and insert lithium during the first and subsequent charge and discharge processes, so that the lithium-ion battery has a higher first coulomb efficiency, battery capacity, energy density and cycle performance; in addition, in the early cycle charge and discharge test, the negative electrode material with an expansion coefficient in a certain numerical range can effectively avoid the destruction of the material structure and mechanical crushing caused by significant volume expansion, thereby extending the battery life. The negative electrode material of the present application can improve the first coulomb efficiency, battery capacity, energy density and cycle performance of lithium-ion batteries, and extend the battery life.

[0073] Lithium-ion batteries complete the charging and discharging process by embedding and de-embedding between the positive and negative electrodes. Specifically, during the charging process, lithium ions are extracted from the positive electrode material and embedded in the corresponding negative electrode material through the electrolyte. At the same time, electrons flow from the positive electrode to the negative electrode through the external circuit. When the lithium-ion battery is discharged, lithium ions are extracted from the negative electrode and re-embedded in the positive electrode material through the electrolyte. At the same time, electrons flow to the positive electrode through the external circuit. The rate and ability of lithium ion embedding and de-embedding are important parameters that determine the life and performance of lithium-ion batteries. For example, for negative electrode materials, the higher the rate of lithium ion embedding and de-embedding, the higher the electrochemical reaction activity and the higher the charge and discharge efficiency. However, if the embedding or de-embedding rate is too high, it will cause deformation and leakage of the electrode material, reducing the cycle life of the material. Silicon-based materials themselves have the property of expansion. The applicant has studied the expansion rate after different numbers of charge and discharge cycles, and measured the lithium removal and insertion ability, lithium removal and insertion rate, and stable lithium removal and insertion ability of the negative electrode material by the rate of change of the expansion rate under a certain number of cycles, so as to evaluate its first efficiency, battery capacity, energy density and cyclability. Specifically, the lithium ion insertion ability and rate during the charging process are measured by the rate of change of the charging expansion rate, such as the first charging expansion coefficient, and the stable lithium insertion ability during the charging process is measured by the second charging expansion coefficient. The discharge expansion rate change rate, for example, the first discharge expansion coefficient, is used to measure the lithium ion deintercalation ability and rate of the negative electrode material in the discharge stage, and the second charging expansion coefficient is used to measure the stable lithium deintercalation ability of the negative electrode material in the discharge stage. The applicant found that when the first charging expansion coefficient is between 0.016 and 0.025 and the second charging expansion coefficient is between 0.0008 and 0.002, the negative electrode material has better lithium intercalation ability and rate as well as stable lithium intercalation ability. When the first discharge expansion coefficient is between 0.020 and 0.030 and the second charging expansion coefficient is between 0.003 and 0.0036, the negative electrode material has better lithium deintercalation ability and rate as well as stable lithium deintercalation ability, which can improve the subsequent stable lithium deintercalation and lithium intercalation cycle of the lithium-ion battery. The highest threshold of the cycling process, the finally prepared lithium-ion battery has a higher first efficiency, battery capacity, energy density and cyclability. When the first charging expansion coefficient is less than 0.016, the second charging expansion coefficient is less than 0.0008, the first discharge expansion coefficient is less than 0.020, and the second charging expansion coefficient is less than 0.003, the negative electrode material has a lower lithium de- and lithium insertion rate, and the battery performance is poor. When the first charging expansion coefficient is higher than 0.025, the second charging expansion coefficient is higher than 0.0008, the first discharge expansion coefficient is higher than 0.020, and the second charging expansion coefficient is higher than 0.003, the lithium ion insertion and de-insertion rate in the negative electrode material is too high, resulting in deformation and leakage of the electrode material. The drastic structural changes can reduce the cycle life of the material.

[0074] It can be understood that in the above embodiment, the first charging expansion coefficient K c1The range is 0.016≤K c1 ≤0.025, specifically it can be 0.016, 0.017, 0.018, 0.019, 0.020, 0.021, 0.022, 0.023, 0.024 or 0.025, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0075] The first discharge expansion coefficient K f1 The range is 0.020≤K f1 ≤0.030, specifically it can be 0.020, 0.021, 0.022, 0.023, 0.024, 0.025, 0.026, 0.027, 0.028, 0.029 or 0.030, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0076] The second charging expansion coefficient K c2 The range is 0.0008≤K c2 ≤0.002, specifically it can be 0.0008, 0.001, 0.0012, 0.0014, 0.0016, 0.0018 or 0.002, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0077] The second discharge expansion coefficient K f2 The range is 0.003≤K f2 ≤0.0036, specifically it can be 0.003, 0.0031, 0.0032, 0.0033, 0.0034, 0.0035 or 0.0036, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0078] In some embodiments, N1=3, N2=20. In the cyclic charge and discharge test, it is found that the change rate of the expansion rate in the first three cycles and the change rate of the circle expansion rate from three to twenty cycles, the negative electrode material is within the above range, can further improve the subsequent stable lithium de-lithium and lithium insertion capabilities of the lithium-ion battery, so that the lithium-ion battery has a higher first coulombic efficiency, battery capacity, energy density and better cycle performance.

[0079] In some embodiments, V c0 、V c1 、V f1 、V c2 、V f2 The expansion rates are obtained by in-situ detection, that is, the expansion rate is tested during the charge and discharge process. The test process is simple and easy to operate.

[0080] In some embodiments, the coating layer includes a carbon layer. The carbon layer can not only alleviate the volume expansion of the negative electrode material, but also enhance the conductivity of the negative electrode material and improve the battery performance.

[0081] In some embodiments, the silicon-based material includes at least one of silicon, silicon oxide, and silicate, wherein the general formula of silicon oxide is SiO x , 0<x≤2, x can be 0.05, 0.2, 0.4, 0.6, 0.8, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 2.0, and of course other values ​​within the above range, which are not limited here. Silicon-based materials are considered to be a promising negative electrode material due to their high theoretical specific capacity, but this type of material has a large volume effect during the lithium insertion and extraction process. Using it as the core material and coating it with a carbon layer can alleviate volume expansion and affect the migration ability and stability of lithium ions. Negative electrode materials with expansion coefficients within the above range have better lithium removal and insertion capabilities, lithium removal and insertion rates, and stable lithium removal and insertion capabilities, and can obtain higher first coulombic efficiency, battery capacity, energy density and cycle performance.

[0082] In some embodiments, based on the mass of the negative electrode material as 100%, the mass of the carbon layer is 2% to 6%, specifically 2%, 2.2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, and of course other values ​​within the above range, which are not limited here. When the carbon layer content is within the above range, it can better alleviate volume expansion and improve the stability of lithium ion migration.

[0083] In a preferred embodiment, the compaction density of the negative electrode material is 1.2 g / cm 3 Up to 1.5g / cm 3 , bulk density is 0.4g / cm 3 Up to 0.65g / cm 3 , true density is 2.0g / cm 3 Up to 2.5g / cm 3 The compacted density can be 1.2g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.40g / cm 3 , 1.45g / cm 3 , 1.50g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here. The specific bulk density can be 0.4g / cm 3 , 0.45g / cm 3 , 0.5g / cm 3 , 0.55g / cm 3 , 0.6g / cm 3 , 0.65g / cm3 Of course, it can also be other values ​​within the above range, which is not limited here. The true density can be 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here. The density of the negative electrode active material affects the energy density and conductivity of the battery. Under this compaction density, apparent density and true density, the battery has a higher energy density and charge and discharge efficiency. The compaction density, apparent density and true density of the negative electrode material are matched, which can improve the stability of lithium removal and lithium insertion of lithium-ion batteries.

[0084] In a preferred embodiment, the compaction density of the negative electrode material (in g / cm 3 ) meets 5.4×10 9 <1 / [1.33π×(extreme value / 2) 3 × compacted density] <1.01×10 10 , the bulk density of the negative electrode material (in g / cm 3 ) meets 9.5×10 9 <1 / [1.33π×(extreme value / 2) 3 × bulk density] <2.8×10 10 , the true density of the negative electrode material (in g / cm 3 ) meets 2.2×10 9 <1 / [1.33π×(extreme value / 2) 3 × true density] <6.0×10 9 , the extreme value unit is cm. When the compacted density, loose density and true density satisfy the above relationship at the same time, the negative electrode material has good volume density energy, and the resistivity of the prepared electrode sheet is low, which is more conducive to realizing the above-mentioned trend of change in the expansion rate of the negative electrode material. Specifically, the particle size is measured by Mastersizer 3000 laser diffraction technology. When the laser beam passes through the dispersed negative electrode material particle sample, the particle size measurement is completed by measuring the intensity of the scattered light. The measured data is then used to analyze and calculate the particle size distribution that forms the scattering spectrum. The particle size corresponding to the highest peak in the particle size distribution diagram is taken as the extreme value. In the above relationship, the compacted density, loose density, true density and extreme value take the values ​​under the corresponding units.

[0085] In a preferred embodiment, the negative electrode material is tested for powder conductivity using a powder conductivity instrument. When the pressure is 20 kN, the tested powder conductivity is greater than 1 S / cm, specifically 1 S / cm, 1.05 S / cm, 1 S / cm, 1.1 S / cm, 1.15 S / cm, 1.2 S / cm, 1.25 S / cm, 1.35 S / cm, 1.4 S / cm, 1.45 S / cm, 1.5 S / cm, 1.55 S / cm, 1.6 S / cm, and of course other values ​​within the above range, which are not limited here. When the powder conductivity meets the above conditions, it has a better lithium ion migration rate.

[0086] In a preferred embodiment, the contact angle of the negative electrode material is 140° to 180°, specifically 140°, 145°, 147°, 150°, 152°, 155°, 157°, 160°, 165, 170°, 180°. The contact angle is within the above range. The negative electrode material has good absorption of the electrode liquid to obtain higher ionic conductivity, and has a lower expansion rate to achieve stable lithium removal and lithium insertion.

[0087] According to another aspect of the present invention, there is provided a method for preparing a negative electrode material, comprising the following steps:

[0088] A first mixed material comprising elemental silicon powder and silicon dioxide powder is prepared, the first mixed material is placed in a microwave reaction furnace, and under vacuum conditions, the temperature in the microwave reaction furnace is raised to 1300° C. to 2000° C. at a heating rate of 15° C. / min to 25° C. / min, a mixed gas is obtained by reaction, and the mixed gas is condensed and then ground to obtain silicon-based material powder; wherein the molar ratio of elemental silicon in the elemental silicon powder to silicon dioxide in the silicon dioxide powder is (1.5-2.5):1;

[0089] The silicon-based material powder is mixed with a carbon source to obtain a second mixed material, and the second mixed material is subjected to laser bombardment treatment to obtain a negative electrode material;

[0090] The negative electrode material includes a silicon-based material core and a coating layer at least partially coated on the surface of the silicon-based material core. The first charging expansion coefficient K of the negative electrode material is c1 , the first discharge expansion coefficient K f1 , the second charging expansion coefficient K c2 , the second discharge expansion coefficient K f2 The following conditions are met:

[0091] 0.016≤K c1 ≤0.025;

[0092] 0.020≤K f1 ≤0.030;

[0093] 0.0008≤K c2 ≤0.002;

[0094] 0.003≤K f2 ≤0.0036;

[0095]

[0096] 3≤N1≤5;

[0097] 4≤N2≤20;

[0098] Among them, V c0 V is the expansion rate of the negative electrode material after the first cycle of charging during the cyclic charge and discharge process; f0 V is the expansion rate of the negative electrode material after the first discharge cycle in the cyclic charge and discharge process; c1 V is the expansion rate of the negative electrode material after the N1th cycle of charging and discharging is completed; V f1 V is the expansion rate of the negative electrode material after the N1th cycle of discharge during the cyclic charge and discharge process; c2 V is the expansion rate of the negative electrode material after the N2th cycle of charging is completed during the cyclic charge and discharge process; f2 It is the expansion rate of the negative electrode material after the N2th discharge in the cyclic charge and discharge process.

[0099] Silicon-based materials are considered to be promising negative electrode materials due to their high theoretical specific capacity. However, this type of material has a large volume effect during the lithium insertion and extraction process, and its drastic structural changes can lead to degradation of the product's cycle performance. Coating the silicon-based material with a coating layer can alleviate volume expansion and affect the migration ability and stability of lithium ions. The prepared core-shell structured negative electrode material with an expansion coefficient within the above numerical range can improve the ability of lithium-ion batteries to smoothly extract and insert lithium during the first and subsequent charge and discharge processes, thereby allowing lithium-ion batteries to have higher first coulombic efficiency, battery capacity, energy density and cycle performance. The present application uses silicon and silicon dioxide as initial raw materials, and utilizes microwave heating to rapidly heat the reaction under vacuum conditions, which is conducive to the rapid reaction of silicon dioxide to generate low-expansion silicon oxide to reduce the silicon dioxide content in the silicon oxide product. At the same time, excess silicon is condensed and collected in the form of gas along with the silicon oxide gas to obtain silicon oxide with a higher silicon content, so that the negative electrode material has excellent lithium removal and lithium insertion capabilities and rates. In addition, the present application uses the silicon-based material powder as the core material, and further improves the stability of lithium ion migration rate and alleviates volume expansion through coating, thereby obtaining a negative electrode material with an expansion coefficient within the above-mentioned range. The negative electrode material has both better and higher lithium removal and lithium insertion capabilities, lithium removal and lithium insertion rates, and stable lithium insertion capabilities, so that the prepared negative electrode material has higher first efficiency, battery capacity, energy density and cyclability, thereby improving the performance and service life of lithium-ion batteries. The present application utilizes laser bombardment for coating. On the one hand, after laser bombardment, a small amount of silicon oxide undergoes disproportionation reaction to generate silicon dioxide and silicon element. The increase of silicon element can further increase the battery capacity. On the other hand, laser bombardment can make the carbon source uniformly coat the silicon-based material powder to form a uniform, smooth, and small specific surface carbon layer, thereby enhancing the conductivity of the negative electrode material. Moreover, laser bombardment for coating can cause the carbon source to be cracked to form a new amorphous structure carbon layer that is firmly adsorbed on the silicon-based material powder. By utilizing the carbon source to coat the silicon-based material, the volume expansion of the silicon-based material during the charging and discharging process can be reduced, and the stability of lithium ion migration can be improved, thereby enhancing the ability of lithium-ion batteries to smoothly remove and insert lithium during the charging and discharging process, thereby improving battery performance and service life.

[0100] In some embodiments, the coating layer includes a carbon layer. The carbon layer can not only alleviate the volume expansion of the negative electrode material, but also enhance the conductivity of the negative electrode material and improve the battery performance.

[0101] In some embodiments, the silicon-based material includes at least one of silicon, silicon oxide, and silicate, wherein the general formula of silicon oxide is SiO x , 0<x≤2.

[0102] In some embodiments, the particle size D50 of the silicon-based material powder is 5μm to 10μm, specifically 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9m, 9.5μm, 10μm, and of course other values ​​within the above range, which are not limited here.

[0103] In some embodiments, the carbon source is selected from one or more of asphalt, natural graphite, and artificial graphite. The above carbon materials are used for laser bombardment treatment to obtain a carbon layer with good electrical conductivity.

[0104] In some embodiments, taking the sum of the masses of the silicon-based material powder and the carbon element in the carbon source as 100%, the mass of the carbon element in the carbon source is 2% to 6%, specifically 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, and of course other values ​​within the above range, which are not limited here.

[0105] In a preferred embodiment, the laser wavelength in the laser bombardment treatment is 1000nm to 1200nm, specifically 1020nm, 1040nm, 1060nm, 1080nm, 1100nm, 1120nm, 1140nm, 1160nm, 1180nm, 1200nm, and of course other values ​​within the above range, which are not limited here.

[0106] In some embodiments, a nanosecond pulse fiber laser is used for laser bombardment treatment, the pulse duration is 60ns to 100ns, the laser bombardment treatment time is 1h to 5h, the pulse duration can be 60ns, 65ns, 70ns, 75ns, 80ns, 85ns, 90ns, 95ns, 100ns, the laser bombardment treatment time can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, of course, it can also be other values ​​within the above range, which is not limited here. Under the above conditions, laser bombardment treatment can be performed to obtain a carbon layer with more uniform coating and good conductivity.

[0107] In some embodiments, the particle size D50 of the silicon dioxide powder is 1 μm to 2 μm, specifically 1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, and of course other values ​​within the above range, which are not limited here. The silicon dioxide powder of this size is conducive to the rapid reaction of generating silicon dioxide.

[0108] In some embodiments, the particle size D50 of the elemental silicon powder is 1 μm to 2 μm, specifically 1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, and of course other values ​​within the above range, which are not limited here. The elemental silicon powder of this size is conducive to the full mixing and contact of the powder and the carbon source.

[0109] In some embodiments, the microwave reaction furnace is evacuated to a vacuum below 1Pa, and then heated to a temperature of 0.05Pa, 0.1Pa, 0.2Pa, 0.4Pa, 0.6Pa, 0.8Pa, 1Pa. Of course, it can also be other values ​​within the above range, which are not limited here. Under the above vacuum conditions, it is beneficial to reduce the silicon dioxide content in the silicon oxide product and obtain silicon oxide with a higher silicon content, so that the negative electrode material has excellent lithium removal and lithium insertion capabilities and rates.

[0110] In some embodiments, the SiO generated by the reaction is condensed under negative pressure. x The silicon element escapes in the form of steam and is introduced into a low temperature place under negative pressure conditions to condense to obtain silicon-based material powder, thereby achieving efficient preparation of silicon-based materials.

[0111] In some embodiments, the microwave reaction time in the microwave reaction furnace is 2 hours to 14 hours, specifically 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, and of course other values ​​within the above range, which are not limited here. The reaction time is controlled within the above range so that the silicon dioxide can react fully.

[0112] According to another aspect of the present invention, Figure 1 As shown, a negative electrode sheet 2 is provided, comprising a negative electrode current collector 21 and a negative electrode active material layer 22 combined on the negative electrode current collector, wherein the negative electrode active material layer comprises the above negative electrode material or a negative electrode material prepared according to the above negative electrode material preparation method.

[0113] In some embodiments, the negative electrode active material layer further includes graphite.

[0114] In some embodiments, the graphite is selected from one or more of natural graphite, artificial graphite, and modified graphite.

[0115] In some embodiments, the modified graphite is selected from expanded graphite, oxidized graphite, or a mixture of the two.

[0116] According to another aspect of the present invention, a lithium-ion battery is provided, wherein the lithium-ion battery comprises the negative electrode sheet as described above.

[0117] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0118] Example 1

[0119] Step 1, take 500g of elemental silicon powder and 500g of silicon dioxide powder (the molar ratio of elemental silicon to silicon dioxide is 2.14:1), put them into a VC mixer for mixing, put them into a microwave reactor (CY-HM1700C-M) after mixing, evacuate the microwave reactor to 0.2Pa, and then increase the temperature to 1600℃ at a heating rate of 20℃ / min, keep it warm for 8h, and obtain a gas containing silicon oxide and elemental silicon, and export the gas through a pipeline to a cold end collector connected to a mechanical pump, and the collector collects a composite material of bulk silicon oxide and elemental silicon, and puts the composite material of bulk silicon oxide and elemental silicon into a ball mill and grinds it into a composite material powder of silicon oxide and elemental silicon; wherein the particle size D50 of the raw material elemental silicon powder is 2μm, the particle size D50 of the raw material silicon dioxide powder is 1μm, and the particle size D50 of the composite material powder of silicon oxide and elemental silicon is 5μm.

[0120] Step 2: Mix the composite material powder of silicon oxide and elemental silicon with asphalt, and bombard the mixture with a nanosecond pulse fiber laser (YLP0.5-80-10, IPG) with a pulse duration of 80ns and a wavelength of 1064nm for 2h to obtain a negative electrode material; wherein, the mass of the carbon element in the asphalt is 5%, taking the sum of the masses of the composite material powder of silicon oxide and elemental silicon and the carbon element in the asphalt as 100%.

[0121] Example 2

[0122] Step 1, take 350g of elemental silicon powder and 500g of silicon dioxide powder (the molar ratio of elemental silicon to silicon dioxide is 1.5:1), put them in a VC mixer for mixing, put them in a microwave reactor after mixing, evacuate the microwave reactor to 1Pa, and then increase the temperature to 1300°C at a heating rate of 20°C / min, and keep it warm for 14 hours to obtain a gas containing silicon oxide and elemental silicon, and export the gas through a pipeline to a cold end collector connected to a mechanical pump. The collector collects a composite material of bulk silicon oxide and elemental silicon, and puts the composite material of bulk silicon oxide and elemental silicon into a ball mill and grinds it into a composite material powder of silicon oxide and elemental silicon; wherein the particle size D50 of the raw material elemental silicon powder is 1μm, the particle size D50 of the raw material silicon dioxide powder is 2μm, and the particle size D50 of the composite material powder of silicon oxide and elemental silicon is 5μm.

[0123] Step 2: Mix the composite material powder of silicon oxide and elemental silicon with natural graphite, and irradiate the mixture with a nanosecond pulse fiber laser (YLP0.5-80-10, IPG) with a pulse duration of 60ns and a wavelength of 1000nm for 1h to obtain a negative electrode material; wherein, the mass of the carbon element is 5%, with the sum of the masses of the composite material powder of silicon oxide and elemental silicon and natural graphite being 100%.

[0124] Example 3

[0125] Step 1, take 580g of elemental silicon powder and 500g of silicon dioxide (the molar ratio of elemental silicon to silicon dioxide is 2.5:1), put them in a VC mixer for mixing, put them in a microwave reactor after mixing, evacuate the microwave reactor to 0.1Pa, and then increase the temperature to 2000℃ at a heating rate of 20℃ / min, keep it warm for 2h, and obtain a gas containing silicon oxide and elemental silicon, and export the gas through a pipeline to a cold end collector connected to a mechanical pump, and the collector collects a composite material of bulk silicon oxide and elemental silicon, and puts the composite material of bulk silicon oxide and elemental silicon into a ball mill and grinds it into a composite material powder of silicon oxide and elemental silicon; wherein the particle size D50 of the raw material elemental silicon powder is 2μm, the particle size D50 of the raw material silicon dioxide powder is 2μm, and the particle size D50 of the composite material powder of silicon oxide and elemental silicon is 5μm.

[0126] Step 2: Mix the composite material powder of silicon oxide and elemental silicon with artificial graphite, and irradiate the mixture with a nanosecond pulse fiber laser (YLP0.5-80-10, IPG) with a pulse duration of 100ns and a wavelength of 1200nm for 5 hours to obtain a negative electrode material; wherein, the sum of the masses of the composite material powder of silicon oxide and elemental silicon and artificial graphite is 100%, and the mass of the carbon element is 5%.

[0127] Example 4

[0128] The only difference from Example 1 is that the mass of the added elemental silicon powder is different, so that the molar ratio of elemental silicon to silicon dioxide is 1.8:1.

[0129] Example 5

[0130] The only difference from Example 1 is that the mass of the added elemental silicon powder is different, so that the molar ratio of elemental silicon to silicon dioxide is 2.2:1.

[0131] Example 6

[0132] The only difference between it and Example 1 is that the heating rate in step 1 is 16° C. / min.

[0133] Example 7

[0134] The only difference from Example 1 is that the heating rate in step 1 is 22° C. / min.

[0135] Example 8

[0136] The only difference between it and Example 1 is that the temperature is raised to 1400° C. in step 1.

[0137] Example 9

[0138] The only difference between it and Example 1 is that the temperature is raised to 1800° C. in step 1.

[0139] Example 10

[0140] The only difference from Example 1 is that the laser bombardment time is 3 hours.

[0141] Embodiment 11

[0142] The only difference from Example 1 is that the laser bombardment time is 4 hours.

[0143] Example 12

[0144] The only difference between the above methods and Example 1 is that the mass of the carbon element in the carbon source is 2%.

[0145] Embodiment 13

[0146] The only difference from Example 1 is that the mass of the carbon element in the carbon source is 4%.

[0147] Comparative Example 1

[0148] The only difference from Example 1 is that the mass of the added elemental silicon powder is different, so that the molar ratio of elemental silicon to silicon dioxide is 1:1.

[0149] Comparative Example 2

[0150] The only difference from Example 1 is that the heating rate in step 1 is 5° C. / min.

[0151] Comparative Example 3

[0152] The only difference from Example 1 is that the heating rate in step 1 is 10° C. / min.

[0153] Comparative Example 4

[0154] The only difference between the embodiment 1 and the embodiment 1 is that chemical vapor deposition is used for carbon coating in step 2. Specifically, step 2 is as follows:

[0155] The composite material powder of silicon oxide and elemental silicon is placed in a chemical vapor deposition furnace, methane gas and inert protective gas are introduced, and carbon deposition coating is performed at 800°C for 5 hours to obtain a silicon-oxygen negative electrode material.

[0156] Comparative Example 5

[0157] The only difference between it and Example 1 is that in step 1, the temperature is raised to 1100° C. for reaction.

[0158] Comparative Example 6

[0159] The only difference between it and Example 1 is that in step 1, the temperature is raised to 2300° C. for reaction.

[0160] Comparative Example 7

[0161] The only difference from Example 1 is that no carbon source asphalt is added in step 2.

[0162] Negative electrode material performance test:

[0163] 1. The negative electrode material prepared in Example 1 was characterized by SEM. The results are as follows: Figure 2 As shown, the prepared negative electrode material is granular, with a particle size of about 5 microns. The negative electrode material prepared in Example 1 is characterized by XRD. Figure 3 As shown, the phase peaks of elemental silicon and amorphous silicon oxide can be observed, while the carbon peak and silicon dioxide peak are not observed to be obvious due to their low content.

[0164] 2. Powder conductivity test: The conductivity of the material under a pressure point of 20KN was tested using a powder resistance test system (Mitsubishi Chemical, Japan, MCP-PD51). The powder conductivities of the negative electrode materials prepared in Examples 1-13 and the negative electrode materials prepared in Comparative Examples 1-7 under 20kN are shown in Tables 1 and 2, respectively.

[0165] 3. Oxygen content test: The oxygen content in the material was tested using an oxygen, nitrogen and hydrogen element analyzer (Elter, ONH-2000). The oxygen content (mass percentage) of the negative electrode materials prepared in Examples 1-13 and the negative electrode materials prepared in Comparative Examples 1-7 are shown in Tables 1 and 2, respectively.

[0166] 4. Carbon content test: The carbon content in the material was tested using an infrared carbon-sulfur analyzer (CSI, Elter, Germany). The carbon content (mass percentage) of the negative electrode materials prepared in Examples 1-13 and the negative electrode materials prepared in Comparative Examples 1-7 are shown in Table 1 and Table 2, respectively.

[0167] 5. Compaction density test: The compaction density of the material was tested in accordance with GB / T 24533-2019. The test equipment used a compaction density meter (McNor, CARVER 4350). The compaction densities of the negative electrode materials prepared in Examples 1-13 and the negative electrode materials prepared in Comparative Examples 1-7 are shown in Tables 1 and 2, respectively.

[0168] VI. True density test: The true density of the material was tested in accordance with GB / T 24533-2019. The test equipment used was a true density tester (BEST, 3H-2000TD). The true densities of the negative electrode materials prepared in Examples 1-13 and the negative electrode materials prepared in Comparative Examples 1-7 are shown in Table 1 and Table 2, respectively.

[0169] VII. Bulk density test: The bulk density was tested using a bulk density tester (Hosokawa Micron, PT-X). The test conditions were: amplitude of 1.5 mm, vibration time of 30 s, and vibration of 1000 times. The bulk densities of the negative electrode materials prepared in Examples 1-13 and the negative electrode materials prepared in Comparative Examples 1-7 are shown in Tables 1 and 2, respectively.

[0170] 8. Contact angle test: The contact angle of the material to water was tested by the sessile drop method. The test equipment used was a contact angle meter (Shanghai Xuan Yi Chuang Xi Industrial Equipment Co., Ltd., XG-CAMB3). The contact angles of the negative electrode materials prepared in Examples 1-13 and the negative electrode materials prepared in Comparative Examples 1-7 are shown in Table 1 and Table 2, respectively.

[0171] IX. Particle size test: The particle size was measured using Mastersizer 3000 laser diffraction technology. Specifically, when the laser beam passes through the dispersed particle sample, the particle size measurement is completed by measuring the intensity of the scattered light. The data is then used to analyze and calculate the particle size distribution of the scattering spectrum, and the particle size corresponding to the highest peak in the particle size distribution diagram is taken as the extreme value. The particle size D50 and extreme value of the negative electrode materials prepared in Examples 1-13 and the negative electrode materials prepared in Comparative Examples 1-7 are shown in Tables 1 and 2, respectively.

[0172] 10. Expansion rate test and battery performance test

[0173] 1.1. Preparation of negative electrode sheet

[0174] The negative electrode material, conductive agent SP, conductive graphite SFG-6 and binder LA133 were mixed in deionized water at a mass percentage of 75%:5%:10%:10% for 8 h, and the mixed slurry was coated on a 12 μm copper foil. After vacuum drying at 60 °C, the slurry was rolled and punched to obtain a 16 cm diameter disc (surface density 43 g cm -2 , compacted density is 1.3 g·cm -2 ), and dried at 85 °C under vacuum for 8 h.

[0175] 1.2 Battery Assembly

[0176] The dried negative electrode was used as the working electrode; metallic lithium was used as the counter electrode, the diaphragm was Celgard2325, and the electrolyte was 1 mol·L -1 LiPF6-EC (ethylene carbonate) / DMC (dimethyl carbonate) / EMC (ethyl methyl carbonate) (wherein the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1) is used to complete the assembly of CR2016 type button half-cells in a glove box filled with high-purity argon.

[0177] 1.3. Battery activation

[0178] The prepared CR2016 button half-cell was placed on a blue power test cabinet (CT3001C) for battery activation, wherein the battery activation included formation, aging and capacity division processes, and the formation conditions were: 0.02C constant current charging to 30 min, standing for 5 min, 0.05C constant current charging for 30 min, standing for 5 min, 0.1C constant current charging for 120 min, standing for 5 min, and 0.2C constant current charging for 180 min; the aging conditions were: placing the battery after charge formation at room temperature for 6 h; the capacity division conditions were: 0.2C constant current charging to 4.2V, then constant voltage charging to 0.01C, standing for 5 min, 0.20C DC discharge to 2.75V, standing for 5 min, 0.5C constant current charging to 4.2V, 4.2V constant voltage charging to 0.01C, standing for 5 min, 0.5C DC discharge to 2.75V, standing for 5 min.

[0179] 1.4. Cyclic charge and discharge test

[0180] The activated CR2016 button half-cell was tested for cyclic charge and discharge using a battery tester. The cyclic charge and discharge conditions were as follows: 0.5C constant current charge to 4.2V, then constant voltage charge to 0.01C, rest for 5 minutes, 0.5C DC discharge to 2.75V, rest for 5 minutes, and cyclic charge and discharge. The first charge specific capacity, first discharge specific capacity, first coulomb efficiency, and capacity retention rate after 50 cycles of each battery are shown in Table 3.

[0181] 1.5. Obtaining the expansion rate of the negative electrode material

[0182] Compared with the negative electrode material, the expansion of other components or parts is negligible during the first 20 cycles of charge and discharge, so the expansion rate of other components or parts in the CR2016 button half-cell can be ignored. Therefore, the expansion rate of the battery body along its thickness direction can be used as the expansion rate of the negative electrode material.

[0183] Specifically, during the cyclic charge and discharge test in step 1.4, the following test and calculation are performed to obtain the expansion rate of the negative electrode material:

[0184] 1) The test steps are as follows: Use a thickness sensor with an accuracy of 0.1 μm to measure the thickness of a CR2016 button half-cell in real time and in situ.

[0185] 2) The expansion rate is calculated as follows:

[0186] Expansion rate = (Δd / h0) × 100%;

[0187] Δd=h x -h0;

[0188] Where h0 is the original thickness of the CR2016 button half-cell, h x The thickness of a CR2016 button half-cell is measured in real time in situ.

[0189] Taking the negative electrode material prepared in Example 1 as an example, the expansion rate curve of the negative electrode material after each cycle of charging and the expansion rate curve of the negative electrode material after each cycle of discharging are shown in FIG. Figure 4 Based on the expansion rate curve of the negative electrode material after each cycle of charging, the first charging expansion coefficient, the second charging expansion coefficient, the first discharge expansion coefficient, and the second discharge expansion coefficient of the negative electrode material prepared in Example 1 are calculated according to the following formula. Specifically: Based on the expansion rate (V c0 ) and the expansion rate at the end of the third cycle of charging (V c1 ) calculates the first charging expansion coefficient based on the expansion rate (V c1 ) and the expansion rate at the end of the 20th cycle of charging (V c2 , calculate the second charging expansion coefficient; based on the expansion rate at the end of the first cycle of discharge (V f0 ) and the expansion rate at the end of the third discharge cycle (V f1 ) calculate the first discharge expansion coefficient; based on the expansion rate (V f1 ) and the expansion rate at the end of the 20th discharge (V f2 ), calculate the second discharge expansion coefficient.

[0190]

[0191] Among them, N1=3, N2=20.

[0192] The charge and discharge expansion coefficients of the negative electrode materials of Examples 1-13 and Comparative Examples 1-7 and the performance parameters of batteries prepared using the negative electrode materials thereof are shown in Table 3.

[0193] Table 1

[0194]

[0195] Table 2

[0196]

[0197] Table 3

[0198]

[0199] It can be seen from Table 1, Table 2 and Table 3 that compared with Comparative Examples 1-7, the battery prepared from the negative electrode material having an expansion coefficient in a certain numerical range (0.016≤first charge expansion coefficient≤0.025, 0.020≤first discharge expansion coefficient≤0.030, 0.0008≤second charge expansion coefficient≤0.002, 0.003≤second discharge expansion coefficient≤0.0036) prepared in Examples 1-13 has high charge specific capacity, high discharge specific capacity, high first coulombic efficiency, and the battery capacity retention rate after 50 cycles is significantly higher than that of the comparative example, and has excellent cycle performance.

[0200] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material comprises a silicon-based material core and a coating layer at least partially coated on the surface of the silicon-based material core. The first charging expansion coefficient K of the negative electrode material is c1 , the first discharge expansion coefficient K f1 , the second charging expansion coefficient K c2 , the second discharge expansion coefficient K f2 The following conditions are met: 0.016≤K c1 ≤0.025; 0.020≤K f1 ≤0.030; 0.0008≤K c2 ≤0.002; 0.003≤K f2 ≤0.0036; 3≤N1≤5; 4≤N2≤20; Among them, the V c0 is the expansion rate of the negative electrode material after the first cycle of charging is completed during the cyclic charge and discharge process; f0 is the expansion rate of the negative electrode material after the first discharge cycle in the cyclic charge and discharge process; c1 is the expansion rate of the negative electrode material after the N1th cycle of charging is completed during the cyclic charge and discharge process; f1 is the expansion rate of the negative electrode material after the N1th discharge cycle is completed during the cyclic charge and discharge process; c2 is the expansion rate of the negative electrode material after the N2th cycle of charging is completed during the cyclic charge and discharge process; f2 The expansion rate of the negative electrode material after the N2th discharge cycle in the cyclic charge and discharge process; The coating layer includes a carbon layer; based on the mass of the negative electrode material being 100%, the mass of the carbon layer is 2% to 6%; The compaction density of the negative electrode material is 1.2 g / cm 3 Up to 1.5g / cm 3 , bulk density is 0.4g / cm 3 Up to 0.65g / cm 3 , true density is 2.0g / cm 3 Up to 2.5g / cm 3 ; The expansion rate of the negative electrode material is tested and calculated as follows: the negative electrode material is made into a negative electrode sheet and assembled into a CR2016 button half-cell, and a cyclic charge and discharge test is performed. During the cyclic charge and discharge test, the expansion rate of the battery body along its thickness direction is taken as the expansion rate of the negative electrode material: 1) The test steps are as follows: Use a thickness sensor with an accuracy of 0.1 μm to measure the thickness of a CR2016 button half-cell in real time and in situ; 2) The expansion rate is calculated as follows: Expansion rate = (Δd / h0) × 100%; Δd=h x -h0; Where h0 is the original thickness of the CR2016 button half-cell, h x The thickness of a CR2016 button half-cell is measured in real time in situ.

2. The negative electrode material according to claim 1, characterized in that N1=3, N2=20; and / or, The V c0 , the V c1 , the V f1 , the V c2 , the V f2 They were obtained by in-situ detection.

3. The negative electrode material according to claim 1 or 2, characterized in that: The silicon-based material includes at least one of silicon, silicon oxide and silicate, and the general formula of the silicon oxide is SiO x , 0<x≤2.

4. The negative electrode material according to claim 3, characterized in that The compaction density of the negative electrode material meets 5.4×10 9 <1 / [1.33π×(extreme value / 2) 3 × compacted density] <1.01×10 10 The bulk density of the negative electrode material meets 9.5×10 9 <1 / [1.33π×(extreme value / 2) 3 × bulk density] <2.8×10 10 The true density of the negative electrode material meets 2.2×10 9 <1 / [1.33π×(extreme value / 2) 3 × true density] <6.0×10 9 , wherein the particle size corresponding to the highest peak in the particle size distribution diagram of the particle size test of the negative electrode material is taken as the extreme value, and the extreme value unit is cm; and / or, The negative electrode material is tested for powder conductivity using a powder conductivity instrument, and when the pressure is 20 kN, the tested powder conductivity is greater than 1 S / cm; and / or, The contact angle of the negative electrode material is 140° to 180°.

5. A method for preparing a negative electrode material, characterized in that: The steps include: A first mixed material comprising elemental silicon powder and silicon dioxide powder is prepared, the first mixed material is placed in a microwave reaction furnace, and under vacuum conditions, the temperature in the microwave reaction furnace is raised to 1300° C. to 2000° C. at a heating rate of 15° C. / min to 25° C. / min, a mixed gas is obtained by reaction, and the mixed gas is condensed and then ground to obtain silicon-based material powder; wherein the molar ratio of elemental silicon in the elemental silicon powder to silicon dioxide in the silicon dioxide powder is (1.5-2.5):1; The silicon-based material powder is mixed with a carbon source to obtain a second mixed material, and the second mixed material is subjected to laser bombardment treatment to obtain the negative electrode material; The negative electrode material comprises a silicon-based material core and a coating layer at least partially coated on the surface of the silicon-based material core. The first charging expansion coefficient K of the negative electrode material is c1 , the first discharge expansion coefficient K f1 , the second charging expansion coefficient K c2 , the second discharge expansion coefficient K f2 The following conditions are met: 0.016≤K c1 ≤0.025; 0.020≤K f1 ≤0.030; 0.0008≤K c2 ≤0.002; 0.003≤K f2 ≤0.0036; 3≤N1≤5; 4≤N2≤20; Among them, the V c0 is the expansion rate of the negative electrode material after the first cycle of charging is completed during the cyclic charge and discharge process; f0 is the expansion rate of the negative electrode material after the first discharge cycle in the cyclic charge and discharge process; c1 is the expansion rate of the negative electrode material after the N1th cycle of charging is completed during the cyclic charge and discharge process; f1 is the expansion rate of the negative electrode material after the N1th discharge cycle is completed during the cyclic charge and discharge process; c2 is the expansion rate of the negative electrode material after the N2th cycle of charging is completed during the cyclic charge and discharge process; f2 The expansion rate of the negative electrode material after the N2th discharge cycle in the cyclic charge and discharge process; The coating layer includes a carbon layer; The compaction density of the negative electrode material is 1.2 g / cm 3 Up to 1.5g / cm 3 , bulk density is 0.4g / cm 3 Up to 0.65g / cm 3 , true density is 2.0g / cm 3 Up to 2.5g / cm 3 ; The expansion rate of the negative electrode material is tested and calculated as follows: the negative electrode material is made into a negative electrode sheet and assembled into a CR2016 button half-cell, and a cyclic charge and discharge test is performed. During the cyclic charge and discharge test, the expansion rate of the battery body along its thickness direction is taken as the expansion rate of the negative electrode material: 1) The test steps are as follows: Use a thickness sensor with an accuracy of 0.1 μm to measure the thickness of a CR2016 button half-cell in real time and in situ; 2) The expansion rate is calculated as follows: Expansion rate = (Δd / h0) × 100%; Δd=h x -h0; Where h0 is the original thickness of the CR2016 button half-cell, h x The thickness of a CR2016 button half-cell is measured in real time in situ.

6. The method for preparing the negative electrode material according to claim 5, characterized in that: The silicon-based material includes at least one of silicon, silicon oxide and silicate, and the general formula of the silicon oxide is SiO x , 0<x≤2.

7. The method for preparing the negative electrode material according to claim 5, characterized in that: The particle size D50 of the silicon-based material powder is 5 μm to 10 μm; and / or, The carbon source is selected from one or more of asphalt, natural graphite, and artificial graphite; and / or, Taking the sum of the mass of the silicon-based material powder and the carbon element in the carbon source as 100%, the mass of the carbon element in the carbon source is 2% to 6%; and / or, The laser wavelength in the laser bombardment treatment is 1000nm to 1200nm; and / or, The laser bombardment treatment is performed using a nanosecond pulse fiber laser, the pulse duration is 60 ns to 100 ns, and the laser bombardment treatment time is 1 h to 5 h.

8. The method for preparing the negative electrode material according to claim 6 or 7, characterized in that: The particle size of the silicon dioxide powder is 1 μm to 2 μm; and / or, The particle size D50 of the elemental silicon powder is 1 μm to 2 μm; and / or, The microwave reaction furnace is evacuated to a vacuum level below 1 Pa, and then heated to a high temperature; and / or, said condensation under negative pressure conditions; and / or, The microwave reaction time in the microwave reaction furnace is 2h to 14h.

9. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer bonded to the negative electrode current collector, characterized in that: The negative electrode active material layer includes the negative electrode material according to any one of claims 1 to 4 or the negative electrode material prepared by the method for preparing the negative electrode material according to any one of claims 5 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Negative active material and recahrgeable lithium battery including the same

    CN110350156A

  • Negative plate and electrochemical device

    CN115377368A

  • Negative electrode material, preparation method thereof and battery

    CN117334859A